Plantar pressure analysis: Identifying risk of foot and ankle injury in soccer players. Issue 6 (24th May 2021) - Ménard, Anne‐Laure; Begon, Mickaël; Barrette, Justin; Green, Benjamin; Ballaz, Laurent; Nault, Marie‐Lyne
Abstract : The aim of this study was to determine whether risk factors for foot or ankle injuries could be identified using quantitative foot measurements. Male and female soccer players of all levels from 9 to 40 years old were included in this cross‐sectional study. Soccer history, foot and ankle function and injury history were investigated. Foot symmetry, length and arch height flexibility and plantar pressure captured with a mat were measured. All variables showing a significant correlation ( P ≤ .05) and the presence of at least one foot or ankle injury were integrated into a multivariate logistic regression model using forward stepwise selection. We recruited 277 players (196 males), and 79 participants had sustained at least one foot or ankle soccer‐related injury. The significant variables were as follows: age, gender, pressure on the lateral heel and on the fourth and fifth metatarsals. Based on the model, the area under the ROC curve was 81.2%. To achieve a specificity of 80%, the corresponding sensitivity was 72.2%. Plantar pressure measurements can objectively assess foot alignment. Increased pressure on the lateral heel and fourth and fifth metatarsal cavovarus foot type represent a risk factor for foot and ankle injuries in soccer. Level of evidence: IV.